pH-Responsive DNA Nanolinker Conjugated Hybrid Materials for Electrochemical Microactuator and Biosensor Applications - Jodat, Yasamin A.; Lotfi, Parisa; Abadi, Parisa Pour Shahid Saeed; Mun, Ji-Young; Seo, Jungmok; Shin, Eun Ae; Jung, Sung Mi; Lee, Chang Kee; Shin, Su Ryon (AMER CHEMICAL SOC, 2018)
Carbon nanotube (CNT)-based composite or hybrid materials have been broadly used for various biomedical applications such as microactuators, sensors, capacitors, and flexible electronic textiles because of their appealing physical and electrical properties and energy-storage functions. However, to enable application-based specific functionalities (e.g., sensing, responding, and deformation) it is essential that smart stimulus responsive elements be incorporated into the CNT-based materials. A pioneering approach in integrating stimulus responsive molecules or linkers is to utilize multistranded DNA structures, such as i-motif DNA with a four-folded structure, which shows reversible conformational changes upon pH alteration. Herein, a pH-responsive CNT-based hybrid material is developed by conjugating i-motif DNA as a pH-responsive nanosized cross-linker. To fabricate microfibers, we spun the i-motif DNA nanolinker-conjugated CNT-based hybrid material in a proton rich coagulation bath. The attained hybrid microfibers are composed of partially aligned nanowires with similar to 50 nm diameters that are formed in the protonation process by self-assembly of the i-motif DNA nanolinker-conjugated CNT-based hybrid material. The hybrid microfibers showed high electrical conductivity (similar to 27 S/cm), excellent capacitance in a biological medium (similar to 59.9 F/g at pH 5 and similar to 47.8 F/g at pH 8), and stable microactuation without creep behavior. Furthermore, the conjugated i-motif DNA in the hybrid microfibers undergoes conformational changes from a four-folded structure (pH 5) to a random coil structure (pH 8), thus enabling unique dual-pH reversibility in the microfibers, namely switchable microporosity, electrochemical redox activity, and hydrogen peroxide sensing activity. Consequently, the designed stimulus-responsive hybrid microfiber can be used for microactuation and biosensing applications.
Keywords: CARBON-NANOTUBE; HYDROGEN-PEROXIDE; MODIFIED ELECTRODE; AMPEROMETRIC BIOSENSOR; GLUCOSE-OXIDASE; REDOX ACTIVITY; COMPOSITE; FIBERS; DISPERSION; SENSORS